2008
DOI: 10.1161/circulationaha.107.709105
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genome-Wide Linkage in US and Australian Twins Identify Novel Genomic Regions Controlling Chromogranin A

Abstract: Background-Chromogranin A (CHGA) triggers catecholamine secretory granule biogenesis, and its catestatin fragment inhibits catecholamine release. We approached catestatin heritability using twin pairs, coupled with genome-wide linkage, in a series of twin and sibling pairs from 2 continents. Methods and Results-Hypertensive patients had elevated CHGA coupled with reduction in catestatin, suggesting diminished conversion of precursor to catestatin. Heritability for catestatin in twins was 44% to 60%. Six hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 44 publications
(53 reference statements)
5
73
1
2
Order By: Relevance
“…Murine Chrna3 overexpression increased CHGA/EAP chimera secretion, and the nicotinic-agonist evoked increase in chimera release was inhibited by catestatin. Although we have not yet determined the precise causal variant in the Chrna3 region, these cellular results suggest a hypothesis unifying our experimental observations as reported previously (O'Connor et al, 2008): Nicotinic agonist stimulation of nAChRs on chromaffin cells releases catestatin, which in negative feedback manner blocks nicotinic secretion. Augmented expression of the crucial ␣3 subunit of the nAChR affecting autonomic function (CHRNA3) may increase the gain of the system, thereby changing the coupling between catestatin modulation of nAChRs and BP.…”
Section: Discussionsupporting
confidence: 79%
“…Murine Chrna3 overexpression increased CHGA/EAP chimera secretion, and the nicotinic-agonist evoked increase in chimera release was inhibited by catestatin. Although we have not yet determined the precise causal variant in the Chrna3 region, these cellular results suggest a hypothesis unifying our experimental observations as reported previously (O'Connor et al, 2008): Nicotinic agonist stimulation of nAChRs on chromaffin cells releases catestatin, which in negative feedback manner blocks nicotinic secretion. Augmented expression of the crucial ␣3 subunit of the nAChR affecting autonomic function (CHRNA3) may increase the gain of the system, thereby changing the coupling between catestatin modulation of nAChRs and BP.…”
Section: Discussionsupporting
confidence: 79%
“…Non-paternity can result in a biased estimation of IBD probability, leading to incorrect linkage results in non-parametric linkage analysis (MacGregor et al, 2000). In fact, DZ twins have been used in linkage mapping of gene expression QTLs (De Moor et al, 2007;Livshits et al, 2007;Perola et al, 2007;O'Connor et al, 2008). Similarly, methods using sib-pairs (i.e.…”
Section: Quantitative Trait Loci (Qtl) Mapping Using Dizygotic Twinsmentioning
confidence: 99%
“…6 Might such variation also change processing of CHGA to its bioactive peptide? We 13 and Stridsberg et al 14 have observed a reciprocal relationship between the circulating concentrations of CHGA and its fragments, likely reflecting processing of the prohormone to its active fragments in plasma.…”
Section: ϫ25mentioning
confidence: 53%